Molecular Interaction Studies on N-Alkanols with DMA in Toluene at 303K - S. Thirumaran; J. Earnest Jayakumar; B. Hubert Dhanasundaram (E-Journal of Chemistry)
The ultrasonic study of velocity, density and viscosity has been measured for the mixtures of n-alkanols, namely; 1-propoanol, 1-butanol and 1-pentanol in toluene with N-N dimethyl acetamide (DMA) at 303K. The experimental data have been used to calculate the acoustical parameters such as adiabatic compressibility (β), intermolecular free length (Lf), free volume (Vf), internal pressure (πi) and acoustic impedance (Z). The excess values of the above parameters have also been evaluated and presented. From the present investigation, it is obvious that a weak molecular association was identified. Mixing of DMA with n alkanols causes dissociation of hydrogen bonded structures of n- alkanols. Also, further addition of DMA with the mixture not only causes dissociation of hydrogen bonded structures of n-alkanols but also a decrease in molecular association between toluene and n-alkanols is observed. The evaluated excess values predict weak molecular interactions existing between DMA-n-alkanols as well as toluene-n-alkanols.